Dialogical kinesis: Edison and the 'print' appearance of Blacksmiths in the Balkans - Grgić, Ana (Early popular visual culture, 2020)
This article presents a new discovery, based on a text published in a local newspaper in Split, Dalmatia in late 1892, which confirms the hypothesis of multiple versions of Edison and Dickson's early Kinetoscope films, in particular, in regards to the Blacksmiths subject. Furthermore, it elucidates the relationship between Edison and announcements of initial moving image shows in Dalmatia and the region, to demonstrate how the inventor's name and fame were frequently associated with the invention of moving image technology. While establishing transnational and transatlantic connections via print and visual media, the article provides further impetus for early cinema scholars to look beyond established figures and narratives, and consider the development of moving images in interstitial spaces around the world such as the Balkans.